Selective nerve root block combined with posterior percutaneous cervical endoscopic discectomy for cervical spondylotic radiculopathy with double nerve root variation: A case report. Issue 12 (March 2020) - Yu, Tong; Zhang, Jun; Wu, Jiu-Ping; Yu, Hai-Chi; Tian, Hai-Qing; Luo, Su-Li; Liu, Qin-Yi
Abstract: Rationale: The aim of this report is to present the technique of selective nerve root blockage combined with posterior percutaneous cervical endoscopic discectomy (PPECD) for cervical spondylotic radiculopathy (CSR). Patient concerns: A 49-year-old female has pain in the skin area of the left scapular, pain in left elbow and limitation of left upper limb movement for 1.5 years. Diagnosis: She was diagnosed with CSR and C6-7 double nerve root variation. Interventions: We used selective nerve root block to determine the lesion segment and applied PPECD to relieve pressure on the patient's nerve roots. Outcomes: The pain symptoms disappeared after the patient was treated with C6-7 nerve root block. Endoscopic displayed C6-7 double nerve root variation on the left side of the spinal cord intraoperative. The neurological function was intact postoperatively and no recurrence of cervical disc herniation during the 5 months' follow-up period. The hospitalization time was 5 days, the operation time was 68.2 minutes and the bleeding volume was 52.6 ml. There was no change in cervical curvature and cervical disc height postoperatively. Japanese Orthopaedic Association score, SF-36 score and Visual Analogue Scale score improved significantly postoperatively. Lessons: The application of selective nerve root blockage combined with PPECD for CSR could achieve satisfactory effect of position and decompression of the injured nerve root. Besides, we recommend that surgery be performed under general anesthesia to minimize patients' emotional stress and discomfort.